2002
DOI: 10.4269/ajtmh.2002.66.2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the malaria control campaign (1993-1998) in the highlands of Madagascar: parasitological and entomological data.

Abstract: Abstract. Malaria transmission in the central highlands of Madagascar was interrupted in the 1960s by a national control program that used DDT indoor spraying and mass treatment with chloroquine. At the end of the 1980s in this region, epidemic malaria reappeared. Italian health authorities provided technical assistance to the National Malaria Control Program since the beginning of the resurgence of malaria in the central highlands. Yearly residual house spraying performed for 5 years (1993)(1994)(1995)(1996)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 4 publications
1
35
0
2
Order By: Relevance
“…The largest reported effect was found in the study by Romi and others, 51 in which an RR for malaria prevalence between the groups with and without coverage by IRS was 0.01 (95% confidence interval = 0.01-0.02), which represented a reduction of 99%. Conversely, the RRs were only approximately 0.9 the study by Charlwood, 52 which indicated a reduction of malaria of only 10%.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The largest reported effect was found in the study by Romi and others, 51 in which an RR for malaria prevalence between the groups with and without coverage by IRS was 0.01 (95% confidence interval = 0.01-0.02), which represented a reduction of 99%. Conversely, the RRs were only approximately 0.9 the study by Charlwood, 52 which indicated a reduction of malaria of only 10%.…”
Section: Resultsmentioning
confidence: 88%
“…Among the 13 studies selected for meta-regression analysis, two studies were randomized control trials (RCTs), 39,40 four were cross-sectional studies comparing malaria parasitemia rates in a population that lived in IRS-covered homes to another group that did not, 35,[41][42][43] and seven were cohort studies that assessed the parasitemia rate before IRS intervention and again at a certain time after IRS. 38,[44][45][46][47][48][49] This classification resulted in seven observations from RCTs (16%), 20 observations from cross-sectional studies (44%), and 18 observations from cohort studies (40%).…”
Section: Resultsmentioning
confidence: 99%
“…NAI is compromised in pregnant women, especially primigravidae, and adults removed from their routine infections apparently lose NAI, at least temporarily. Interventions that reduce exposure below a level capable of maintaining NAI risk the possibility of catastrophic rebound, as occurred in the highlands of Madagascar in the 1980s, with epidemic malaria killing more than 40,000 people (259). Routine exposure to hyper-to holoendemic malaria protects a majority of individuals while killing a minority.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 40,000 people died in the epidemic. With Italian aid, DDT spraying was re-introduced for a 5 year period in the 1990s; this brought A. funestus and malaria back under control (13). The intention now is to maintain surveillance and to re-spray any foci of disease which may emerge.…”
Section: Africamentioning
confidence: 99%